The Identity Enigma: Denial of First Nations Women's Rights to Identity. - King, Jessie Capri (Author); Hoffman, Ross (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2011)
The concept of Indian status is problematic and is experienced as a phenomenon that can be both positive and negative. The phenomenon investigated in this research is that of status loss for various reasons: a) marrying-out, b) unknown and unstated paternity, and c) second generation cut-off. At this point in history the Indian Act is being questioned regarding gender discrimination that restricts Status transmission for First Nations women in comparison to First Nations men. Throughout this research Bill C-3 was proposed, read in parliament, and eventually passed as legislation to promote gender equality in Indian Registration. On January 31st 2011 Bill C-3 became law and is now know as the Gender Equity in Indian Registration Act. However, it is important to note that the struggle for equality is not complete with the addition of this amendment for reasons to be discussed in this research. As a First Nations woman experiencing the phenomena that result from the Indian Act's restrictions of status transmission for First Nations women I wanted to hear from other women in my situation. I also wanted to hear from women experiencing other forms of status transmission restrictions and give them the opportunity to have a voice against legislation that attempts to undermine them. The Indian Act elicits different responses, perceptions, and emotions when it comes to defining who is an Indian' and who is not eligible. It is these varying opinions that I sought out with the co-researchers in this study in order to provide a document that is inclusive and safe for discussion. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1740948